Unsupervised Multi-Label Image and Texture Segmentation based on Optimal Feature Representation - Mehmet Cem Catalbas (Tehnički Vjesnik, 2019)
In this paper, an adaptive and robust unsupervised texture segmentation algorithm is proposed. One of the novelties of this proposed algorithm is to determine optimal sub-image size by pattern analysis and another one is optimizing segmentation process by providing the most successful representation of pattern on images. The realization of the algorithm consists of various stages. Firstly, the parameters of regional minima and maxima for images are obtained to extract real pattern information about images. In the next stage, these outputs are combined to each other to calculate the centroid of distribution of patterns. The input image and several texture analysis features are analyzed in the light of this pattern information. Then, the dimension reduction process is performed by the PCA with Horn's parallel analysis method before the data clustering is applied to the dataset. This method allows optimal representation of data after dimension reduction process. The output image is improved by subjecting it to various morphological operations which are called an adaptive morphological mask and the performance of the proposed algorithm is compared with other texture segmentation algorithms.